(untitled) (Research, Society and Development, 2022)
Menopause corresponds to a phase of great relevance in the maturity of female human life. This indispensable event, however, can present unpleasant symptoms and disturbances. Food is one of the main factors that deserves attention in this period, due to the greater efficiency in preparing the body to better deal with such discomforts. Therefore, this scientific article has the objective of presenting how nutritional therapy can be an adjuvant in helping women’s quality of life during this phase. The research is, therefore, an integrative review, based on materials already published, such as scientific articles, periodicals and magazines, located in databases such as Scielo, Biblioteca Virtual da Saúde and Capes in the period from 2016 to 2022. The main foods that help in the reduction of pathologies associated with menopause are fruits, vegetables and legumes, oilseeds rich in phytoestrogens, soy and foods rich in isoflavones, fish, flaxseed and other foods rich in omega 3, sprouted legumes rich in coumestans and foods rich in calcium and vitamin D. Thus, throughout the study, the understanding was established that the consumption of vegetables, fruits and whole grains are of paramount importance for the prevention of risk factors for disorders associated with menopause.